THE IMPACT OF UPBRINGING AND FAMILY SOCIOECONOMIC STATUS ON THE LIFE SKILLS OF HIGH SCHOOL STUDENTS AT SHANDONG ZIBO SCHOOL A - Qiushuo Hou; Panjanat Vorawattanachai (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The purposes were to 1) To study the life skills of high school students at Shandong Zibo School A, 2) To examine the relationship between upbringing and life skills of high school students at SHANDONG ZIBO SCHOOL A, and 3) To explore the impacts of family socioeconomic status on life skills of high school students at Shandong Zibo School A. The sample size was 383 students. Research instruments included questionnaires, statistics (frequency, percentage, ANOVA, Multiple Regression Analysis, and Pearson correlation coefficient). 1. The life skills of high school students at Shandong Zibo School A have a high level, 2. The relationship between upbringing and life skills of high school students at Shandong Zibo School A was found to be moderately positive and statistically significant at the 0.01 level, with a correlation coefficient of 0.65, 3. The family socioeconomic status impacts on life skills of high school students at Shandong Zibo School A results indicate that 1) Family income had significant on high school students' life skills 2) father's education level has not significant on high school students' life skills, 3) mother's education level has not significant on high school students' life skills, 4) father's occupation has significant on high school students' life skills and 5) mother's occupation has significant on high school students' life skills.